Terrorism Experts’ Predictions Regarding the Effects of the COVID-19 Pandemic on the Activities of Violent Non-State Actors - Veilleux-Lepage, Yannick (Perspectives on terrorism, 2022)
This article seeks to systematically collate the assessments and predictions of terrorism experts through a survey of 142 terrorism experts’ evaluations. In light of the recent emergence of a growing number of policy and peer-reviewed publications dealing with the potential impact of the COVID-19 pandemic on the activities of violent non-state actors—whether in terms of propaganda, radicalization, violent action, or recruitment and mobilization—this article seeks to evaluate the degree of consensus within the field of terrorism studies on these effects. Because terrorism experts play an important role in the formulation of national security decisions and the shaping of public debates, and their analyses of current and future threats frequently influence policy considerations, this study provides insight into the prevalent attitudes among terrorism experts in the midst of the pandemic. This is important as these prevailing attitudes may shape future research in the field of terrorism studies and subsequently impact governmental policies.